2017
DOI: 10.21577/0103-5053.20170173
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Six Synthetic Dyes in Sports Drinks by Dispersive Solid-Phase Extraction and HPLC-UV-Vis

Abstract: A simple, fast and efficient method was developed for determination of six synthetic dyes (Tartrazine, Sunset Yellow, Amaranth, Ponceau 4R, Indigo Carmine and Brilliant Blue) in sports drinks using dispersive solid-phase extraction (d-SPE) with the polymeric sorbent Oasis ® HLB. Sample preparation using d-SPE permitted to simplify the procedure and use less sorbent in comparison with SPE. The use of a syringe for the elution step make this easier and avoid the use of a manifold. High performance liquid chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…In a study, Zamani Mazdeh et al separated 8 synthetic colors by reverse chromatography in which the LOD and LOQ ranged from 0.357 to 0.873 and 1.082 to 2.646 mg/kg, respectively, which were higher compared with the current study. Floriano et al reported 0.15 and 1.154 mg/L for LOD and LOQ, respectively, for synthetic colors in sport drinks using RP-HPLC, which are higher compared with the current study (23,24). Feng et al have reported higher LOD for tartrazine and Ponceau 4R colors as well as lower LOD for Indigo, Sunset yellow, Allura red, Quinoline yellow, Brilliant blue, and Carmoisine compared with our study (25).…”
Section: Expansion and Validation Of Ip-hplc-dad And Spe Methodscontrasting
confidence: 77%
“…In a study, Zamani Mazdeh et al separated 8 synthetic colors by reverse chromatography in which the LOD and LOQ ranged from 0.357 to 0.873 and 1.082 to 2.646 mg/kg, respectively, which were higher compared with the current study. Floriano et al reported 0.15 and 1.154 mg/L for LOD and LOQ, respectively, for synthetic colors in sport drinks using RP-HPLC, which are higher compared with the current study (23,24). Feng et al have reported higher LOD for tartrazine and Ponceau 4R colors as well as lower LOD for Indigo, Sunset yellow, Allura red, Quinoline yellow, Brilliant blue, and Carmoisine compared with our study (25).…”
Section: Expansion and Validation Of Ip-hplc-dad And Spe Methodscontrasting
confidence: 77%
“…Although several studies determined the content of sugars in isotonic sport drinks or their capability of hydration, among others, only a few studies were focused on the determination of food colorants in sport drinks . In that context, this work provides new information concerning the content of colorants in this type of commercial drink.…”
Section: Introductionmentioning
confidence: 99%
“…To further evaluate the performance of the present method, four previously reported methods for determining sunset yellow [38][39][40][41] in different matrices were compared with the present method and the detailed results are summarized in Table 2. The linear range and LOD were comparable to those in the previously reported methods, demonstrating the reliability of the proposed method.…”
Section: Comparison Of the Proposed Methods With The Reported Methodsmentioning
confidence: 99%